Integrating Fiqh al-Bi’ah into Project-Based Learning to Enhance Environmental Character in Islamic Higher Education - Sulaeman, Sulaeman; Ahmad, Ahmad; Ridwan, Irmayanti (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Environmental degradation and climate crises continue to escalate globally, while Islamic higher education has yet to effectively integrate religious environmental ethics into its pedagogy. This study addresses the lack of integration of Islamic environmental values into higher education curricula, particularly within Muhammadiyah institutions. The aim of this research is to examine whether a project-based learning (PjBL) model centered on fiqh al-bi’ah (Islamic environmental jurisprudence) effectively enhances the environmental character of university students. Employing a qualitative Classroom Action Research approach, 40 sixth-semester students participated in community-based environmental projects over one semester, and their progress was assessed through pre- and post-intervention evaluations across cognitive, affective, and psychomotor domains. Findings indicated significant improvements: cognitive understanding of fiqh al-bi’ah increased from 61.2% to 89%, affective attitudes toward environmental stewardship improved from 58.7% to 87.5%, and psychomotor skills rose from 43.5% to 74%. Furthermore, students demonstrated enhanced awareness, empathy, and commitment to Islamic environmental ethics. Overall, this study contributes to eco-Islamic pedagogy by demonstrating the efficacy of integrating religious principles into practical environmental education. It also suggests avenues for future research on long-term behavior changes and broader implementation in diverse educational settings.